ALGORITHM FOR ENSURING AND IMPLEMENTING SOCIAL PROJECTS IN THE CONTEXT OF GLOBALISATION (COMPARATIVE ASPECT) - Sarancha, Iryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
In the practice of Ukrainian public institutions today, there is a significant presence of financial support from international funds to ensure the implementation of social projects. This topic in the education sector also has its roots and peculiarities of use at different levels of educational services. And one of the most pressing issues in our practice of implementing socially significant projects on the basis of higher education institutions and within the framework of NGOs was the issue of a phased algorithm for implementing such projects. Therefore, in this scientific review, we have considered the importance and significance of social projects in the public and public sector on the example of Ukraine and EU countries; compared the main directions of international and Ukrainian social projects analysed the issues of financial support for relevant project activities. This analysis allowed us to present the main algorithms of interaction between public funds, business and the community at the national and international level, as well as to develop an algorithm for ensuring social projects for their further implementation in the context of global access to information and grant support at all levels.